Discharge against Medical Advice at a Teaching Hospital in Ghana - Surazu Bayor; Albert Kojo Korsah (Nursing Research and Practice)
Introduction. Discharge against medical advice is a global phenomenon where patients voluntarily terminate their consent to medical care before the medical team declares them fit for discharge. The phenomenon adversely affects the delivery of quality health care. Methods. A retrospective study was conducted at a Ghanaian teaching hospital involving patients who were admitted to the emergency settings within a 2 years period. Data were retrieved from the hospital records and patients discharged against medical advice were identified and studied. Data were cleaned and coded with Excel application and analyzed with SPSS version 23. Results. A total of 8,565 admissions were made into the ward within the period under review with 210 patients been discharged against medical advice. The prevalence rate was 2.5% with high prevalence seen in male and younger populations. Fractures and head injuries were the commonest conditions for which patients requested to be discharged against medical advice, whilst financial constrains and preference for herbal treatment were the major factors for which patients requested to be discharged against medical advice. Conclusion. Discharge against medical advice exists and negatively affects the delivery of quality health care in the Ghanaian health sector. Education especially towards at-risk groups such as the younger populations and patients with fractures as well as effective communication between medical team and patients and their families are some proposed measures to reducing the prevalence and negative impacts associated with discharges against medical advice.